Potential for Personalization - Teevan, Jaime; Dumais, Susan; Horvitz, Eric (ACM Transactions on Computer-Human Interaction, 2010)
Current Web search tools do a good job of retrieving documents that satisfy the most common intentions associated with a query, but do not do a very good job of discerning different individuals’ unique search goals.We explore the variation in what different people consider relevant to the same query by mining three data sources: (1) explicit relevance judgments, (2) clicks on search results (a behavior-based implicit measure of relevance), and (3) the similarity of desktop content to search results (a content-based implicit measure of relevance). We find that people’s explicit judgments for the same queries differ greatly. As a result, there is a large gap between how well search engines could perform if they were to tailor results to the individual, and how well they currently perform by returning results designed to satisfy everyone.We call this gap the potential for personalization. The two implicit indicators we studied provide complementary value for approximating this variation in result relevance among people. We discuss several uses of our findings, including a personalized search system that takes advantage of the implicit measures by ranking personally relevant results more highly and improving click-through rates.